Comparison of automated red cell exchange transfusion and simple transfusion for the treatment of children with sickle cell disease acute chest syndrome. Issue 12 (2nd September 2013) - Saylors, Robert L.; Watkins, Benjamin; Saccente, Suzanne; Tang, Xinyu
Abstract Background Both simple transfusion (ST) of packed red blood cells and automated red cell exchange (RCE) are used in the treatment of acute chest syndrome (ACS). We report our experience using each of these modalities for the treatment of ACS. Methods Retrospective chart review of patients with ACS treated with ST only (51 episodes, ST group) or RCE performed either at diagnosis (U‐RCE group, 15 episodes) or after ST (ST + RCE group, 15 episodes). Results The mean clinical respiratory score (CRS) at diagnosis was significantly higher in the U‐RCE group than in the ST group, but there were no significant differences among the other groups. The CRS and WBC each decreased significantly after simple transfusion in the ST group and after RCE in the U‐RCE group, but both the CRS and WBC increased significantly, and the mean platelet count fell significantly, after simple transfusion in the ST + RCE group. Only patients in the ST + RCE group required mechanical ventilation. There were no significant differences in length of stay (LOS) or total hospital charges among any of the groups, probably due to the small sample size. Conclusions We conclude that the CRS identifies the patients who are most severely affected with ACS, and that upfront RCE is a safe and effective treatment for these patients. Additional work is needed to develop a method to predict which of the apparently less severely affected patients will fail to improve after simple transfusion and should receive upfront RCE. Pediatr Blood Cancer 2013;60:1952–1956. © 2013 Wiley Periodicals, Inc.